Analisis Peran Tingkat Pendidikan dan Platform Komunikasi dalam Menunjang Produktivitas Kerja Karyawan Work From Anywhere (WFA) - Luthfi Baihaqy; Diah Priharsari; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
The Covid-19 pandemic has hampered the movement of people in their daily activities, so it is necessary to make some adaptations, especially in the work system. Besides that, the Covid-19 pandemic also has accelerated digital transformations, especially in the industrial and corporate sectors. Many companies are currently implementing a remote work system or commonly known as Work From Anywhere (WFA). The existence of this remote work system can also increase employee work productivity. There are various factors that affect employee work productivity, especially in the application of the WFA work system. This study aims to determine the role of educational level and the use of communication platforms in supporting employee productivity during the WFA period. This study uses mixed methods (qualitative and quantitative) or commonly known as the mix method with an exploratory sequential design approach. Data collection was carried out to WFA employees through semi-structured interviews with 10 informants and a survey by distributing questionnaires to 120 respondents. Further analysis was carried out using thematic analysis, quantitative descriptive analysis, one-way ANOVA test, and multiple linear regression methods. The results of this study is that the level of education does not directly affect the productivity of WFA employees. However, the knowledge gained at the educational level can support employee work productivity during the WFA period. Meanwhile, the communication platform has proved to be an important role in supporting employee productivity in the WFA work system.